“Community Philosophy”: a Transformational Youth Work Practice? - Graeme Tiffany (Sociétés et Jeunesses en Difficulté)
Community Philosophy (CP) is a new methodology adapted from an educational approach called Philosophy for Children (P4C). P4C has been used in schools for many years but only recently adapted by social workers for use in a community context. Groups of young people use a stimulus, typically an image, as a starting point for a Community of Enquiry. In this, the social worker, trained as a CP facilitator, encourages deep exploration of the issues and problems affecting the young people. Key to the process is that young people determine the questions to be examined and are encouraged to engage with each others’ opinions in a critical and collaborative manner.The study explores the findings of a project set up specifically to promote Community Philosophy. The context of the work is one of an area with high levels of antisocial behaviour (both perceived and real). The project facilitated dialogue between young people and older residents (of whom many were intolerant toward them) and also between young people and service providers e.g. the police.The study found that the young people valued highly the opportunity to work with this methodology. It enabled them to explore critically issues and problems affecting them and as identified by them. Several of these enquiries translated into tangible benefits for the young people although these had more to do with improving their sense of well-being than their material life conditions. Foremost were improved relationships with adults in the community and with the police.An unanticipated outcome was the challenges that arose for the workers using this methodology. Institutional constraints and social policy prescriptions, it emerged, made it difficult to respond in the flexible manner that Community Philosophy seems to demand.This poses further questions for the training of workers, the democratisation of organisations and the process of working to deliver often highly prescribed social policy outcomes. Without a philosophical approach in all areas of social intervention, the effectiveness of CP in building young people’s self-esteem and transferable critical thinking skills can be inhibited.Ultimately, Community Philosophy is not so much a mechanism that can deliver more fundamental transformation; instead, it can be seen as a tool that can inform the action that needs to be taken in order to assist young people in becoming autonomous and learning to become agents of change in their own right.